Short-term effects of percutaneous electrical nerve stimulation on pain and muscle function in patients undergoing anterior cruciate ligament surgery: a randomized clinical trial - Caballero-López, Julio; Navarro-Santana, Marcos; Almazán-Polo, Jaime; García-Sanz, Fernando; Díaz-Arribas, María José; Minaya-Muñoz, Francisco; Romero-Morales, Carlos (Frontiers in Rehabilitation Sciences, 2025)
IntroductionAnterior cruciate ligament (ACL) reconstruction surgery is associated with the presence of anterior knee pain and knee extension weakness. Percutaneous electrical nerve stimulation (PENS) is a minimally invasive technique with the objective of neuromodulating the symptoms derived from the intervention. The objective of the study is to analyze the short-term effect of the use of the PENS technique in patients undergoing ACL surgery.Materials and MethodsA randomized clinical trial was carried out at the CEMTRO clinic in Madrid with 70 participants (N = 70) where the effect of the PES intervention in combination with a rehabilitation program (n = 35) was compared against a control group of rehabilitation (n = 35). The study analyzed changes in pain intensity, pressure pain threshold (PPT) of the vastus medialis, vastus lateralis, quadriceps and patellar tendons, isometric knee extension strength and range of motion of the knee.ResultsDifferences were determined in the PENS group compared to the rehabilitation group immediately after the first intervention in the reduction of pain intensity through the VAS scale and in knee extension isometric strength (p < 0.05). Both groups showed differences after 12 weeks in the range of motion of the knee in knee flexion and extension, as well as in the PPT of the patellar tendon.ConclusionThe PENS intervention combined with a rehabilitation program compared to an isolated rehabilitation program showed a short-term reduction in pain intensity and an increase in isometric strength in knee extension in patients undergoing ACL surgery.Clinical Trial Registration[ClinicalTrials.gov], identifier [NCT05606250].